Meaning making and fostering radical hope: applying positive psychology to eco-anxiety research in youth - Malboeuf-Hurtubise, Catherine; Léger-Goodes, Terra; Herba, Catherine M.; Bélanger, Nadia; Smith, Jonathan; Marks, Elizabeth (Frontiers in Child and Adolescent Psychiatry, 2024)
The consequences of human activity on climate change are increasingly apparent. For example, they are causing ecological degradation and affecting human and animal health (1). Rightly so, it is considered as the most important challenge of this century (2). Researchers in psychology and mental health developed an interest in the direct and indirect effects of climate and ecological change on people’s psychological wellbeing, which is referred to a concept described as eco-anxiety or eco-distress (3). It is worth emphasizing that the climate issues are taking a larger place in the school curriculum for youth in elementary, middle and high schools (8). Youth are thus increasingly aware of the major threat and understandably report legitimate concerns and worries (9). For some youth, eco-anxiety leads to greater involvement and activism, as can be seen by the international movement set out and led by youth activist Greta Thunberg (10). However, eco-anxiety can also lead to feelings of hopelessness and disengagement (11). Despite contributing the least to the climate and ecological crises, youth will be most affected by the impacts, and will carry the burden of the climate crisis throughout their lives (9). Researchers, educators and mental health professionals must therefore find ways to foster youth psychosocial wellbeing and resilience alongside ensuring that their voices are heard. To this end, it is vital that young people feel able to openly discuss climate change and associated issues alongside the distressing thoughts and feelings they engender. This can be supported by using various psychological approaches to develop effective interventions. Researchers and clinicians in child mental health could gain from drawing from research in positive psychology to develop such interventions. In this review and commentary, we will outline how eco-anxiety and child psychological wellbeing can be framed within a positive psychology framework, including the relevance of self-determined motivation. Insights from interventions based on positive psychology including exercises to foster hope, forgiveness and meaning making will also be discussed. We will highlight how such interventions can be adapted as powerful tools to foster child wellbeing and cope with their eco-anxiety.